Molecular cloning of a diacylglycerol kinase isozyme predominantly expressed in human retina with a truncated and inactive enzyme expression in most other human cells - Masayuki Kai; Fumio Sakane; S Imai; Ikuo Wada; Hideo Kanoh (1994)
In order to clone novel diacylglycerol kinase (DGK) isozymes, we first obtained a DGK-related cDNA fragment by polymerase chain reaction using the human hepatoma cell line HepG2 mRNA and degenerated primers. The amplified fragment was subsequently used as a probe for screening the cDNA library from HepG2 cells. We obtained a cDNA clone coding for a novel DGK isozyme (designated DGK gamma) comprised of 791 amino acid residues. The amino acid sequence of DGK gamma was 52 and 62% identical to those of previously sequenced porcine 80-kDa and rat 90-kDa enzymes, respectively. DGK gamma, although initially cloned from the HepG2 cDNA libraries, was unexpectedly expressed in the human retina abundantly and to a much lesser extent in the brain. Other human tissues, including the liver and HepG2 cells, contained extremely low levels of DGK gamma mRNA. Furthermore, HepG2 cells and most of the human tissues except for the retina and brain expressed a truncated DGK gamma with an internal deletion of 25 amino acid residues (Ile451-Gly475). When transfected into COS-7 cells, the nontruncated cDNA gave phosphatidylserine-dependent DGK activity with no apparent specificity with regard to the acyl compositions of diacylglycerol. In contrast the truncated cDNA failed to give DGK activity in spite of the expression of its mRNA and enzyme protein in COS cells, thus demonstrating that the truncated DGK gamma is catalytically inactive. The sequence comparison of the three cloned DGKs revealed the presence of four highly conserved regions including the two sets each of EF-hand and zinc finger structures. Although the implication of the catalytically inactive form of DGK gamma remains unknown, this work further demonstrates the occurrence of multiple animal DGK isozymes with a conserved basic structure but with markedly different expression patterns depending on the cell types.